No increased risk of herpes zoster found in cirrhotic patients: a nationwide population-based study in Taiwan. - Ping-Hsun Wu; Yi-Ting Lin; Chun-Nan Kuo; Wei-Chiao Chang; Wei-Pin Chang (PLoS ONE)
Background The association between liver cirrhosis (LC) and herpes zoster has rarely been studied. We investigated the hypothesis that LC, known as an immunodeficiency disease, may increase the risk of herpes zoster using a national health insurance database in Taiwan. Materials and methods The study cohort included cirrhotic patients between 1998 and 2005 (n = 4667), and a ratio of 1:5 randomly sampled age- and gender-matched control patients (n = 23,335). All subjects were followed up for 5 years from the date of cohort entry to identify whether or not they had developed herpes zoster. Cox proportional-hazard regressions were performed to evaluate 5-year herpes zoster-free survival rates. Results Of all patients, 523 patients developed herpes zoster during the 5-year follow-up period, among whom 82 were LC patients and 441 were in the comparison cohort. The adjusted hazard ratio (AHR) of herpes zoster in patients with LC was not higher (AHR: 0.77, 95% confidence interval: 0.59-1.01, p = 0.06) than that of the controls during the 5-year follow-up. No increased risk of herpes zoster was found in LC patients after stratification by age, gender, urbanization level, income, geographic region, and all comorbidities. Conclusions This large nationwide population-based cohort study suggests that there is no increased risk for herpes zoster among people who have LC compared to a matching population.